An Occupational Profile of People Injured in Accidents at Work in the Polish Construction Industry. (2017) - Hoła, Bożena; Szóstak, Mariusz
Abstract: The construction industry in Poland and in the world is characterized by a high level of threat to the life and health of workers. In accident processes, a man exists in a triple role, namely: a decision maker, a perpetrator of an accident and a victim. Statistical data published by the Central Statistical Office regarding the causes of accidents indicates that human causes account for around 60% of all reported cases. Identification of the factors affecting the accident rate and also the direct causes of accidents is the first step in determining the directions of preventive action. The aim of the research conducted by the authors of this article is to present the occupational characteristics of people injured in accidents at work in the Polish construction industry. The article presents the results obtained from the analysis of occupational accidents that occurred in the years 2008-2014 in five voivodships of Poland, namely: Kujawsko-Pomorskie, Slaskie, Lubelskie, Dolnoslaskie and Lubuskie. The paper identifies and examines the impact of the following characteristics: the employment status of a victim, occupation, age, length of service, preparation of the employee to perform duties at a workplace and the size of an enterprise in which the accident took place. 485 occupational accidents were analysed, 37% of which were fatal accidents, 61% were severe, and 2% were light.